A method for preparing a gel electrolyte by in-situ polymerization of a high-pressure-resistant monomer at room temperature with a multifunctional additive

CN119241750BActive Publication Date: 2026-10-20NANKAI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411488065.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2026-10-20
Estimated Expiration
2044-10-24

Smart Images

  • Figure CN119241750B_ABST
    Figure CN119241750B_ABST
Patent Text Reader

Abstract

The application relates to a method for preparing a gel electrolyte by in-situ polymerization of high-pressure-resistant monomers at room temperature under the induction of a multifunctional additive, belonging to the technical field of new energy materials and devices, wherein high-pressure-resistant polymerization monomers, a plasticizer and a multifunctional additive are mixed to form a homogeneous precursor solution 1; an initiator and the plasticizer are mixed to also form a homogeneous precursor solution 2; the precursor solutions 1 and 2 are mixed to obtain a homogeneous precursor solution 3; and the precursor solution 3 is injected into a battery shell of a high-pressure, high-capacity positive electrode and a high-capacity negative electrode, and in-situ polymerization is carried out at room temperature (20 DEG C-35 DEG C) to obtain a high-specific-energy gel electrolyte-based solid-state battery. The gel electrolyte is formed by monomers which should be polymerized by heating, and is formed at room temperature under the action of a trace amount of multifunctional additive; compared with ordinary heating polymerization, the gel electrolyte has the advantages of more uniform distribution, fewer side reactions, reduced energy consumption, a higher electrochemical stability window and better compatibility with a negative electrode, and forms a high-specific-energy solid-state lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of new energy materials and devices technology, specifically involving a gel electrolyte that can be used to prepare a high-voltage resistant monomer by inducing in-situ polymerization at room temperature through multifunctional additives, and can be matched with high-voltage, high-capacity positive electrode and high-capacity negative electrode for assembling high-energy-density solid-state lithium battery. Background Technology

[0002] Batteries, as a crucial energy storage method and power support for the new energy industry, are of great significance to the realization of the national dual-carbon strategy. Currently, the energy density of commercially used lithium iron phosphate / graphite battery systems has reached over 300Wh / kg, approaching the theoretical limit and far from meeting the ever-increasing range requirements, thus necessitating an increase in battery energy density. Simultaneously, the liquid electrolytes used in existing batteries mostly possess intrinsic flammability and leakage risks, posing safety hazards. Therefore, developing high-safety, high-energy-density lithium batteries based on solid-state and quasi-solid-state electrolytes is a vital means of upgrading and replacing battery systems.

[0003] Gel electrolytes, composed of a polymer matrix and a liquid plasticizer, have been developed as a quasi-solid-state electrolyte. Combining the advantages of all-solid-state electrolytes and liquid electrolytes, they represent the most promising solid-state electrolytes for current applications. In-situ polymerization allows for good contact between the solid electrolyte and both the positive and negative electrodes, forming ion pathways to match the high-load positive electrode, making it a highly promising method for gel electrolyte preparation. However, to achieve high-energy-density solid-state batteries, the electrolyte needs a wide electrochemical window to match the high-voltage, high-capacity positive electrode material, placing extremely high demands on the polymerizable monomers. The most common polymerizable monomers capable of withstanding high voltage possess ester groups and carbon-carbon double bond conjugated structures, requiring polymerization to be initiated above 50°C. However, the precursor solution often suffers from uneven heating and thermal flow, resulting in uneven distribution of the gel electrolyte after polymerization. Simultaneously, heating significantly increases side reactions between the positive and negative electrodes and the electrolyte, limiting the application of common high-voltage resistant monomers in practical production.

[0004] Therefore, this invention, through the addition of Lewis acid-based multifunctional additives, improves the electrochemical window to match the high-voltage positive electrode and protects the high-capacity negative electrode, while reducing energy consumption and completing in-situ polymerization at room temperature. It is a highly promising method for preparing gel electrolytes for high-energy-density solid-state batteries. Summary of the Invention

[0005] To address the problems existing in the heating polymerization process of high-voltage resistant monomers in the prior art, and the design requirements of high-energy-density solid-state batteries, this invention provides a method for preparing a gel electrolyte that can match high-voltage, high-capacity positive and high-capacity negative electrodes by inducing the in-situ polymerization of high-voltage resistant monomers at room temperature through multifunctional additives, in order to assemble high-energy-density solid-state lithium batteries.

[0006] The technical solution for implementing the present invention is as follows:

[0007] This invention provides a method for preparing a gel electrolyte that can match high-pressure, high-capacity positive and negative electrodes by inducing in-situ polymerization of high-pressure resistant monomers at room temperature using multifunctional additives, comprising the following steps:

[0008] (1) Mix and dissolve the polymer monomer, plasticizer and multifunctional additive to form a homogeneous precursor solution 1;

[0009] (2) Mix and dissolve the initiator and plasticizer to form a homogeneous precursor solution 2;

[0010] (3) Mix precursor solutions 1 and 2 to form homogeneous precursor solution 3;

[0011] (4) Inject the precursor solution 3 into the battery casing and allow it to stand at room temperature (20℃-35℃) for in-situ polymerization to obtain a gel electrolyte solid battery. The battery uses high-voltage, high-capacity inorganic materials, including but not limited to any one of lithium-rich manganese-based, nickel-cobalt-manganese-based, and lithium cobalt oxide as the positive electrode, and any one of high-capacity lithium metal, lithium-based alloy, and silicon-carbon as the negative electrode.

[0012] Preferably, the dosage is as follows, in parts by mass:

[0013] Monomer: 1-30 parts;

[0014] Plasticizer: 60-98.5 parts;

[0015] Multifunctional additive: 0.1-10 parts;

[0016] Initiator: 0.1-3 parts.

[0017] Preferably, the polymerizable monomer has an ester group and a carbon-carbon double bond conjugated structure, including but not limited to isoprene tetraacrylate (PETEA) and ethoxylated trimethylolpropane triacrylate (ETPTA).

[0018] Preferably, the plasticizer is a liquid electrolyte that can withstand high voltage, and the formulation includes, but is not limited to, lithium difluorooxalate borate (LiDFOB) with the addition of fluoroethylene carbonate (FEC) / methyl trifluoroethyl carbonate (FEMC).

[0019] Preferably, the multifunctional additive is Lewis acid, which has the functions of forming complexes with polymerizing monomers, improving polymerization activity, enhancing the electrochemical stability window, and protecting the negative electrode, including but not limited to tri(pentafluorobenzene)borane (TPFPB).

[0020] Preferably, the initiator is an azo thermal initiator, including but not limited to azobisisobutyronitrile (AIBN).

[0021] Preferably, the battery casing includes, but is not limited to, commercially available XR2032 assembled batteries, and the electrolyte precursor solution is used in an amount of 10μL-100μL.

[0022] Preferably, the battery casing includes, but is not limited to, one of the following: pouch battery, prismatic battery, cylindrical battery, stacked battery, and wound battery.

[0023] Preferably, the room temperature standing temperature is 20℃-35℃, and the standing time is 3h-48h.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The Lewis acid-based multifunctional additive developed in this invention has the functions of reducing the polymerization temperature of high-pressure polymerizable monomers, improving the electrochemical window of the system, and protecting the negative electrode.

[0026] (2) The present invention initiates high-pressure resistant monomer polymerization with ester group and carbon-carbon double bond conjugated structure at room temperature. It greatly improves the problems of common heating polymerization conditions, including (i) uneven heating causing the precursor solution to flow and not be evenly distributed; (ii) uneven heating causing burst polymerization; (iii) liquid phase components volatilizing inside the battery when heated. It also has the advantages of reducing high-temperature side reactions and reducing energy consumption.

[0027] (3) The gel electrolyte prepared by the present invention can be matched with high voltage, high capacity positive electrode and high capacity negative electrode to realize high specific energy solid battery. Attached Figure Description

[0028] Figure 1 This is a comparison of the polymerization behavior of samples without additives (Comparative Example 1) and with additives (TPFPB) at room temperature (20℃-35℃) as a function of standing time.

[0029] Figure 2 This is a comparison of the uniformity of gel electrolyte distribution after polymerization at room temperature (TPFPB) (Example 1) and at heated polymerization (60°C) (Comparative Example 1);

[0030] Figure 3 This is a comparison graph of the linear sweep voltammetry (LSV) curves of room temperature polymerization (TPFPB) (Example 2) and heated polymerization (60°C) (Comparative Example 2);

[0031] Figure 4 This is a comparison graph of the coulombic efficiency of Li-Cu in room temperature polymerization (TPFPB) (Example 3) and heated polymerization (60°C) (Comparative Example 3).

[0032] Figure 5The charge-discharge curves of the first cycle (0.1C) and the second cycle (0.1C) of the half-cell and full cell of room temperature polymerization (TPFPB) (Example 4) with lithium-rich manganese-based cathode and lithium metal anode are shown.

[0033] Figure 6 This is a comparison chart of capacity retention rate versus cycle number for full cells (0.2C) using lithium-rich manganese-based cathode and lithium metal anode, obtained by room temperature polymerization (TPFPB) (Example 4) and heated polymerization (60°C) (Comparative Example 4). Detailed Implementation

[0034] The present invention will be further illustrated below with reference to the accompanying drawings and specific examples. The following examples are for illustrative purposes only and should not be construed as limiting the scope of the present invention. The scope of protection of the present invention is not limited to the following embodiments.

[0035] Example 1

[0036] A method for preparing a gel electrolyte capable of producing high-voltage, high-capacity positive and negative electrodes by inducing in-situ polymerization of high-voltage resistant monomers at room temperature using multifunctional additives is described below:

[0037] (1) Mix and dissolve 15mg of high-pressure resistant monomer PETEA, 5mg of multifunctional additive TFPB and 661μL of plasticizer to form a homogeneous precursor solution 1.

[0038] (2) Mix and dissolve 10 mg of initiator AIBN and 200 μL of plasticizer to form a homogeneous precursor solution 2;

[0039] (3) Take 20 μL of precursor solution 2 with a pipette and add it to precursor solution 1 to form homogeneous precursor solution 3. The preferred injection tool is a pipette with a volume of 100 μL.

[0040] (4) Let the precursor solution 3 in the vial stand at room temperature (20℃-35℃) until the in-situ polymerization is completed, and obtain the optical image of the gel electrolyte;

[0041] (5) The precursor solution 3 that was not allowed to stand in Example 1 was used to assemble SS-SS half-cells. The SS-SS half-cells were assembled with stainless steel gaskets (SS) as both the positive and negative electrodes to observe the polymerization inside the cells. The amount of precursor solution 3 was 50 μL. After the cells were assembled under a pressure of 0.85 tons, they were allowed to stand at room temperature (20℃-35℃) for 24 hours to allow in-situ polymerization to complete. The separator was Celgard 2500, and the preferred injection tool was a pipette with a volume of 100 μL.

[0042] Figure 1The results show the polymerization of precursor solution 3 in the vials of Example 1 and Comparative Example 1 after standing at room temperature for 10 hours. The addition of multifunctional additives can significantly induce the polymerization of high-pressure resistant monomers at room temperature. Figure 2 The SS-SS half-cell in Example 1 was left to stand at room temperature for 24 hours, and the SS-SS half-cell in Comparative Example 1 was kept at 60°C for 6 hours before the separator was removed. Example 1 avoids the problem of uneven distribution of gel electrolyte caused by uneven heating and volatilization of liquid components.

[0043] Example 2

[0044] The precursor solution 3 from Example 1, which was not allowed to stand, was used to assemble an SS-Li half-cell. The electrochemical stability window of the SS-Li half-cell was tested by assembling a stainless steel gasket (SS) as the positive electrode and a Li sheet with a diameter of 14 mm and a thickness of 450 μm as the negative electrode. The amount of precursor solution 3 used was 50 μL. After the cells were assembled under a pressure of 0.85 tons, they were allowed to stand at room temperature (20℃-35℃) for 24 h to allow in-situ polymerization to complete. The separator was Celgard 2500, and the preferred injection tool was a pipette with a volume of 100 μL.

[0045] An SS-Li half-cell was used for electrochemical window testing, and after assembly, it achieved a voltage of 0.2 mV / s. -1 LSV curves were obtained by testing with an electrochemical workstation at a scan rate of 2.5-8V. Figure 3 The LSV curves for Example 2 and Comparative Example 2 are shown. The electrochemical window of Example 2 is greater than 6V, which is significantly higher than that of Comparative Example 2.

[0046] Example 3

[0047] The precursor solution 3 from Example 1, which was not allowed to stand, was used in the Li-Cu half-cell assembly. The coulombic efficiency of the Li-Cu half-cell was tested by assembling a copper foil (Cu) as the positive electrode and a Li sheet with a diameter of 14 mm and a thickness of 450 μm as the negative electrode. The amount of precursor solution 3 used was 50 μL. After the cells were assembled under a pressure of 0.85 tons, they were allowed to stand at room temperature (20℃-35℃) for 24 h to allow in-situ polymerization to complete. The separator was Celgard 2500, and the preferred injection tool was a pipette with a volume of 100 μL.

[0048] The Li-Cu half-cell used for coulombic efficiency testing was assembled at 0.5 mA cm⁻¹. -2 0.5mAh cm -2 Run the loop. Figure 4 The coulombic efficiency of Li-Cu in Example 3 and Comparative Example 3 is as follows: the coulombic efficiency of Example 3 is 96.50%, which is significantly better than that of Comparative Example 3 (93.71%).

[0049] Example 4

[0050] Battery assembly was performed using the untreated precursor solution 3 from Example 1. The battery casing was a commercially available XR2032 assembled battery. The positive electrode was a lithium-rich manganese-based material, and the negative electrode was lithium metal. The total positive electrode diameter was 10 mm, and the charge capacity was 15 mg / cm³. -2 The negative electrode is a Li sheet with a diameter of 10 mm and a thickness of 50 μm. The amount of precursor solution 3 added is 15-20 μL. After the battery is assembled under a pressure of 0.85 tons, it is allowed to stand at room temperature (20℃-35℃) for 24 hours to allow in-situ polymerization to complete. The separator is Celgard 2500. The preferred injection tool is a pipette with a volume of 100 μL.

[0051] The assembled full battery was activated at 0.1C for 3 cycles, followed by charge-discharge cycles at 0.2C. 1C = 250 mAh g -1 . Figure 5 The above are the charge / discharge curves for the first and second cycles of Example 4. The discharge capacity in the first cycle exceeds 250 mAh g. -1 Reaching 269.6mAh g -1 It has the feasibility of high specific energy. Figure 6 The capacity retention rate changes during full-cell charge-discharge cycles of Example 4 and Comparative Example 4 are compared. The cycle performance of Example 4 is significantly better than that of Comparative Example 4.

[0052] Comparative Example 1

[0053] A method for preparing a gel electrolyte compatible with high-pressure, high-capacity positive and negative electrodes through in-situ heating polymerization includes the following steps:

[0054] (1) Mix and dissolve 15mg of high-pressure resistant monomer PETEA and 664μL of plasticizer to form a homogeneous precursor solution 1;

[0055] (2) Mix and dissolve 10 mg of initiator AIBN and 200 μL of plasticizer to form a homogeneous precursor solution 2;

[0056] (3) Take 20 μL of precursor solution 2 with a pipette and add it to precursor solution 1 to form homogeneous precursor solution 3. The preferred injection tool is a pipette with a volume of 100 μL.

[0057] (4) Let the precursor solution 3 in the vial stand at room temperature (20℃-35℃) to obtain an optical image;

[0058] (5) The precursor solution 3 that was not allowed to stand in Comparative Example 1 was assembled into an SS-SS half-cell. The SS-SS half-cell was assembled with stainless steel gaskets (SS) as both the positive and negative electrodes to observe the polymerization inside the cell. The amount of precursor solution 3 was 50 μL. After the cell was assembled under a pressure of 0.85 tons, it was transferred to an oven and heated (60°C) for 6 hours until the in-situ polymerization was completed. The separator was Celgard 2500, and the preferred injection tool was a pipette with a volume of 100 μL.

[0059] Comparative Example 2

[0060] The precursor solution 3 from Comparative Example 1, which was not allowed to stand, was used to assemble an SS-Li half-cell. The electrochemical stability window of the SS-Li half-cell was tested by assembling a stainless steel gasket (SS) as the positive electrode and a Li sheet with a diameter of 14 mm and a thickness of 450 μm as the negative electrode. The amount of precursor solution 3 used was 50 μL. After the cell was assembled under a pressure of 0.85 tons, it was transferred to an oven and heated (60 °C) for 6 hours to allow in-situ polymerization to complete. The separator was Celgard 2500, and the preferred injection tool was a pipette with a volume of 100 μL.

[0061] An SS-Li half-cell was used for electrochemical window testing, and after assembly, it achieved a voltage of 0.2 mV / s. -1 The LSV curves were obtained by testing with an electrochemical workstation at a scan rate of 2.5-6V. Figure 3 The LSV curves for Example 2 and Comparative Example 2 are shown. The electrochemical window of Comparative Example 1 is <5V, which is significantly lower than that of Example 2.

[0062] Comparative Example 3

[0063] The precursor solution 3, which was not allowed to stand in Comparative Example 1, was used to assemble a Li-Cu half-cell. The coulombic efficiency of the Li-Cu half-cell was tested by assembling a copper foil (Cu) as the positive electrode and a Li sheet with a diameter of 14 mm and a thickness of 450 μm as the negative electrode. The amount of precursor solution 3 used was 50 μL. After the cell was assembled under a pressure of 0.85 tons, it was transferred to an oven and heated (60 °C) for 6 hours to allow in-situ polymerization to complete. The separator was Celgard 2500, and the injection tool was preferably a pipette with a volume of 100 μL.

[0064] The Li-Cu half-cell used for coulombic efficiency testing was assembled at 0.5 mA cm⁻¹. -2 0.5mAh cm -2 Run the loop. Figure 4 The coulombic efficiencies of Li-Cu in Example 3 and Comparative Example 3 are as follows: the coulombic efficiency of Comparative Example 3 is 93.71%, which is significantly lower than that of Example 3 (96.50%).

[0065] Comparative Example 4

[0066] Battery assembly was performed using the untreated precursor solution 3 from Comparative Example 1. The battery casing was a commercially available XR2032 assembled battery. The positive electrode was a lithium-rich manganese-based material, and the negative electrode was lithium metal. The total positive electrode diameter was 10 mm, and the charge was >15 mg / cm³. -2 The negative electrode is a Li sheet with a diameter of 10 mm and a thickness of 50 μm. The amount of precursor solution 3 added is 15-20 μL. After the battery is assembled under a pressure of 0.85 tons, it is transferred to an oven and heated (60℃) for 6 hours to allow in-situ polymerization to complete. The separator is Celgard 2500. The preferred injection tool is a pipette with a volume of 100 μL.

[0067] The assembled full battery was activated at 0.1C for 3 cycles, followed by charge-discharge cycles at 0.2C. 1C = 250 mAh g -1 . Figure 6 The capacity retention rate changes during full-cell charge-discharge cycles of Example 4 and Comparative Example 4 are shown. The cycle performance of Comparative Example 4 is significantly weaker than that of Example 4.

[0068] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and optimizations can be made without departing from the principle of the present invention, including improvements and optimizations to high-pressure resistant polymerizable monomers, plasticizers, Lewis acid-based multifunctional additives, and initiators with ester groups and carbon-carbon double bond conjugated structures. These improvements and optimizations should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing gel electrolyte solid-state batteries by in-situ polymerization of high-voltage resistant monomers induced by multifunctional additives at room temperature, characterized in that, Includes the following steps: (1) Mix and dissolve the polymer monomer, plasticizer and multifunctional additive to form a homogeneous precursor solution 1; (2) Mix and dissolve the initiator and plasticizer to form a homogeneous precursor solution 2; (3) Mix precursor solutions 1 and 2 to form homogeneous precursor solution 3; (4) Inject the precursor solution 3 into the battery casing and allow it to stand at room temperature of 20 ℃ - 35 ℃ for in-situ polymerization to obtain a gel electrolyte solid battery. The battery uses any one of lithium-rich manganese-based, nickel-cobalt-manganese-based, and lithium cobalt oxide as the positive electrode and any one of lithium metal, lithium-based alloy, and silicon-carbon as the negative electrode. The raw material usage by weight is as follows: Monomer: 1-30 parts; Plasticizer: 60-98.5 parts; Multi-purpose additive: 0.1 - 10 parts; Initiator: 0.1 - 3 parts; The plasticizer is a liquid electrolyte that can withstand high voltage and is obtained by adding fluoroethylene carbonate (FEC) / methyl trifluoroethyl carbonate (FEMC) to lithium difluorooxalate borate (LiDFOB). The multifunctional additive is tri(pentafluorobenzene)borane TFPB; The polymer monomer is pentaerythritol tetraacrylate (PETEA).

2. The method for preparing a gel electrolyte solid-state battery by in-situ polymerization of high-voltage resistant monomers induced by a multifunctional additive according to claim 1, characterized in that, The volume of electrolyte precursor solution 3 is 10 μL - 100 μL.

3. The method for preparing a gel electrolyte solid-state battery by in-situ polymerization of high-voltage resistant monomers induced by a multifunctional additive according to claim 1, characterized in that, The battery casing is selected from one of the following: pouch battery, square battery, cylindrical battery, stacked battery, and wound battery.

4. The method for preparing a gel electrolyte solid-state battery by in-situ polymerization of high-voltage resistant monomers induced by a multifunctional additive according to claim 1, characterized in that, The room temperature for standing is 20℃ - 35℃, and the standing time is 3h - 48h.

5. The method for preparing a gel electrolyte solid-state battery by in-situ polymerization of high-voltage resistant monomers induced by a multifunctional additive according to claim 1, characterized in that, The initiator is an azo thermal initiator, azobisisobutyronitrile (AIBN).

Citation Information

Patent Citations

  • Gel electrolyte as well as preparation method and application thereof

    CN113224370A

  • Gel electrolyte for silicon-carbon material, preparation method of gel electrolyte and battery

    CN116284523A